Kidney derived apolipoprotein M and its role in acute kidney injury - Bisgaard, Line S.; Christensen, Pernille M.; Oh, Jeongah; Torta, Federico; Füchtbauer, Ernst-Martin; Nielsen, Lars Bo; Christoffersen, Christina (Frontiers in Pharmacology, 2024)
Aim: Apolipoprotein M (apoM) is mainly expressed in liver and in proximal tubular epithelial cells in the kidney. In plasma, apoM associates with HDL particles via a retained signal peptide and carries sphingosine-1-phosphate (S1P), a small bioactive lipid. ApoM is undetectable in urine from healthy individuals but lack of megalin receptors in proximal tubuli cells induces loss of apoM into the urine. Besides this, very little is known about kidney-derived apoM. The aim of this study was to address the role of apoM in kidney biology and in acute kidney injury.Methods: A novel kidney-specific human apoM transgenic mouse model (RPTEC-hapoM TG ) was generated and subjected to either cisplatin or ischemia/reperfusion injury. Further, a stable transfection of HK-2 cells overexpressing human apoM (HK-2-hapoM TG ) was developed to study the pattern of apoM secretion in proximal tubuli cells.Results: Human apoM was present in plasma from RPTEC-hapoM TG mice (mean 0.18 μM), with a significant increase in plasma S1P levels. In vitro apoM was secreted to both the apical (urine) and basolateral (blood) compartment from proximal tubular epithelial cells. However, no differences in kidney injury score was seen between RPTEC-hapoM TG and wild type (WT) mice upon kidney injury. Further, gene expression of inflammatory markers (i.e., IL6, MCP-1) was similar upon ischemia/reperfusion injury.Our study suggests that kidney-derived apoM is secreted to plasma, supporting a role for apoM in sequestering molecules from excretion in urine. However, overexpression of human apoM in the kidney did not protect against acute kidney injury.